Favorable Effects of Tacrolimus Monotherapy on Myasthenia Gravis Patients - Fan, Zhirong; Li, Zunbo; Shen, Faxiu; Zhang, Xueping; Lei, Lin; Su, Shengyao; Lu, Yan; Di, Li; Wang, Min; Xu, Min; Da, Yuwei (Frontiers in Neurology, 2020)
Background and purpose: Tacrolimus (TAC) has been proven to be a rapid-acting, steroid-sparing agent for myasthenia gravis (MG) therapy. However, evidence related to the effectiveness of TAC alone is rare. Therefore, this study was performed to investigate the effect of TAC monotherapy in MG patients. Methods: Forty-four MG patients who received TAC monotherapy were retrospectively analyzed. A mixed effect model was used to analyze improvements in MG-specific activities of daily living scale (MG-ADL), quantitative MG score (QMG) and MG-ADL subscores. Kaplan-Meier analysis was used to estimate the cumulative probability of minimal manifestations (MM) or better. Adverse events (AEs) were recorded for safety analyses. Results: Of the patients receiving TAC monotherapy, MG-ADL scores were remarkably improved at 3, 6 and 12 months compared with scores at baseline (mean difference and 95% CIs: -3.29 [-4.94, -1.64], -3.97 [-5.67, -2.27] and -4.67 [-6.48, -2.85], respectively). QMG scores significantly decreased at 6 and 12 months, with mean differences and 95% CIs of -4.67(-6.88, -2.45) and -5.77 (-7.55, -4.00), respectively. Estimated median period to achieve ‘MM or better’ was 5.0 (95% CIs, 2.8, 7.2) months. Ocular MG (OMG) and generalized MG (GMG) showed similar therapeutic effects in cumulative probabilities of ‘MM or better’ (P value = 0.764). A better response was observed in MG-ADL subscores for ptosis and bulbar symptoms. AEs occurred in 37.5% of patients and were generally mild and reversible. Conclusions: TAC monotherapy is a promising option to rapidly alleviate all symptoms of MG, especially for ptosis and bulbar symptoms.